2016
DOI: 10.3389/fphar.2016.00279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Commercially Available Cannabidiol Formulations for Use in Electronic Cigarettes

Abstract: Since 24 states and the District of Columbia have legalized marijuana in some form, suppliers of legal marijuana have developed Cannabis sativa products for use in electronic cigarettes (e-cigarettes). Personal battery powered vaporizers, or e-cigarettes, were developed to deliver a nicotine vapor such that smokers could simulate smoking tobacco without the inherent pathology of inhaled tobacco smoke. The liquid formulations used in these devices are comprised of an active ingredient such as nicotine mixed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…Furthermore, two separated studies have highlighted the discrepancy between the declared labelled concentrations of cannabinoids and the real contents. Indeed, Pearce et al analysed two commercial marijuana e-liquids claiming to contain 3.3 mg/mL CBD and found that the real contents were around twice as much 22 . In 2017, FDA carried out tests on the chemical content of CBD in commercially available products confirming this label inaccuracy 23 .…”
mentioning
confidence: 99%
“…Furthermore, two separated studies have highlighted the discrepancy between the declared labelled concentrations of cannabinoids and the real contents. Indeed, Pearce et al analysed two commercial marijuana e-liquids claiming to contain 3.3 mg/mL CBD and found that the real contents were around twice as much 22 . In 2017, FDA carried out tests on the chemical content of CBD in commercially available products confirming this label inaccuracy 23 .…”
mentioning
confidence: 99%
“…Although e-liquids used in electronic cigarettes are commonly sold and labeled as containing nicotine many are also available that are labeled to contain other active ingredients such as cannabinoids [7, 18]. The evaluation of the three e-liquids, only labeled “Blueberry B Juice”, “Regular B Juice” and “Vampire B Juice” demonstrates that designer drugs such as MDMB-FUBINACA can be found in commercially available electronic cigarette products.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available e-liquids containing marijuana extracts and cannabidiol have been reported [7, 18]. In October 2015, Shanks KG presented an abstract at the annual Society of Forensic Toxicology meeting [19] that identified the presence of cannabimimetic drugs as the active ingredients in two e-liquids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of electronic cigarettes (E-cig) has recently been increasing among adolescents and young adults [54][55][56]. E-cig usage or "vaping" contains E-liquid carrier components, flavorings, and marijuana product with cannabidiol (CBD) formulations [57][58][59][60]. In anecdotal stories, the use of medical marijuana, in particular vaping with CBD oil may be linked to improvement of refractory pulmonary sarcoidosis [61].…”
Section: Acute Sarcoidosismentioning
confidence: 99%